Implementation of IoT in Inventory Management and Logistics at the Business Incubator Center of the Kosgoro Institute of Business and Informatics 1957 - Angellia, Filda; Firmansyah, Boy; Purwandari, Nuraini; Steven Rahmat, Mars (Publisher Cv. Inara, 2025)
Inventory management and logistics are crucial aspects in the operation of business incubator centers, especially in ensuring the efficient availability and distribution of resources. This research aims to develop and implement an Internet of Things (IoT)-based system in inventory management and logistics at the IBIK57 Innovation Center and Business Incubator Center. The system is designed to provide automation solutions in goods tracking, stock monitoring, and asset distribution optimization using RFID sensor technology, QR codes, and cloud-based communication. The research methods used include literature studies, user needs analysis, IoT-based system design, implementation, and system performance evaluation. RFID sensors and QR codes are used to detect the presence and movement of goods in real-time, while the data obtained is sent to a cloud-based server for processing and analysis. With this system, it is hoped that inventory management will be more accurate, reduce the risk of asset loss, and increase the operational efficiency of business incubator centers. The results show that the application of IoT in inventory management and logistics is able to increase efficiency by up to 40% in stock recording and asset tracking compared to manual methods. In addition, the system also provides users with real-time access to manage inventory in a more transparent and integrated manner. In conclusion, the use of IoT in inventory management and logistics can be an innovative solution in improving the effectiveness of resource management in academic and business environments.